(untitled) - Crankshaw, Edward (London, 1963)
The downfall of the Habsburg monarchy was more than just the end of a great and powerful dynasty. It meant the destruction of the old European order and marked a turning point in world history
Keywords: Austria,Nước Áo; History,Lịch sử; Franz Joseph I, 1848-1916,Vương triều Fanz Joseph đệ nhất, 1848-1916